Effectiveness and Safety of Two Consecutive Cycles of Single Embryo Transfer Compared With One Cycle of Double Embryo Transfer: A Systematic Review and Meta-Analysis - Peng, Yangqin; Ma, Shujuan; Hu, Liang; Wang, Xiaojuan; Xiong, Yiquan; Yao, Minghong; Tan, Jing; Gong, Fei (Frontiers in Endocrinology, 2022)
Objective: To date, evidence regarding the effectiveness and safety of two consecutive cycles of single embryo transfer (2SETs) compared with one cycle of double embryo transfer (DET) has been inadequate, particularly considering infertile women with different prognostic factors. Our aim was to comprehensively summarize the evidence comparing 2SETs with DET. Methods: PubMed, Embase, Cochrane Library databases, ClinicalTrails.gov and the WHO International Clinical Trials Registry Platform were searched up to March 22, 2022. Peer-reviewed, English-language randomized controlled trials (RCTs) and observational studies (OS) comparing outcomes of 2SETs with DET in infertile women with their own oocytes and embryos were included. Two authors independently conducted study selection, data extraction and bias assessment. Mantel-Haenszel random-effects model was used for pooling RCTs, and Bayesian design-adjusted model was conducted to synthesis the results from both RCTs and OS. Main results: Twelve studies were finally included. Compared with the DET, 2SETs were associated with a similar cumulative live birth rate (LBR; 48.24% vs. 48.91%, OR 0.97, 95% Credible interval (CrI): 0.89–1.13, 2=0.1796; four RCTs and six observational studies; 197,968 women), and a notable lower cumulative multiple birth rate (MBR; 0.87% vs. 17.72%, OR 0.05, 95% CrI 0.02–0.10, 2=0.1036; four RCTs and five observational studies; 197,804 women). Subgroup analyses revealed a significantly increase in cumulative LBR (OR 1.33, 95% CrI 1.29–1.38, 2=0) after two consecutive cycles of single blastocyst transfer compared with one cycle of double blastocyst transfer. Moreover, a lower risk of cesarean section, antepartum haemorrhage, preterm birth, low birth weight, and neonatal intensive care unit admission but a higher gestational age at birth and birth weight were found in the 2SETs group. Conclusion: Compared to the DET strategy, 2SETs results in a similar LBR while simultaneously reducing the MBR and improving maternal and neonatal adverse outcomes. The 2SETs strategy appears to be especially beneficial for women aged ≤ 35 years and for blastocyst transfers.